Development of disaster nursing competency assessment instruments - Pandawa, Rugaya Munawar; Saleh, Fatmah M; Muhammad, Ramli (International Journal of Public Health Science (IJPHS), 2025)
It is important to ensure that nurses have sufficient skills and knowledge to handle emergency situations. This competency assessment can help improve nurses' readiness to face disasters and emergency situations that may occur. To develop an unobtrusive (observation) instrument for assessing disaster nursing competency which refers to the International Council of Nurses (ICN) disaster nursing competency framework, especially earthquake and volcano disasters. The starting date for the design of the disaster nursing competency assessment instrument was 2023. Then, the implementation of the research to test the instrument, which had been validated by experts using disaster nursing practice simulations, was conducted for a month from February to March 2023. The research design uses Design-Based, the sample criteria were active student status, emergency nursing, and disaster management courses. The total number of respondents was 80 students, and in the initial stage of testing the instrument during disaster simulation observations, a limited sample of 20 respondents was taken at random and assessed by five lecturers as raters. The instrument development stage started with the specification of the ICN disaster nursing competency assessment instrument. The Aiken index for the unobtrusive observation technique instrument with competency assessment rubric is high, valid, and met reliability requirements. Multifaceted analysis compared students, items, and lecturers from small and large samples. The analysis reveals that students' difficulty levels vary according to the assessing lecturer, with some mastering all items and others only mastering specific ones.